Lactose hydrolysis by ß-galactosidase covalently immobilized to thermally stable biopolymers - Elnashar, Magdy; Yassin, M. (Humana Press, Inc., 2009)
Lactose has been hydrolyzed using covalently immobilized ß-galactosidase on thermally stable carrageenan coated with chitosan (hydrogel). The hydrogel's mode of interaction was proven by Fourier transform infrared spectroscopy, differential scanning calorimetry (DSC), and Schiff's base formation. The DSC thermogram proved the formation of a strong polyelectrolyte complex between carrageenan and chitosan followed by glutaraldehyde as they formed one single peak. The modification of carrageenan improved the gel's thermal stability in solutions from 35 °C to 95 °C. The hydrogel has been proven to be efficient for ß-galactosidase immobilization where 11 U/g wet gel was immobilized with 50% enzyme loading capacity. Activity and stability of free and immobilized ß-galactosidase towards pH and temperature showed marked shifts in their optimum pH from 4.5-5 to 5-5.5 and temperature from 50 °C to 45-55 °C after immobilization, which reveals higher catalytic activity and reasonable stability at wider pHs and temperatures. The apparent K m of the immobilized enzyme increased from 13.2 to 125 mM, whereas the V max increased from 3.2 to 6.6 µmol/min compared to the free enzyme, respectively. The free and immobilized enzymes showed lactose conversion of 87% and 70% at 7 h, respectively. The operational stability showed 97% retention of the enzyme activity after 15 uses, which demonstrates that the covalently immobilized enzyme is unlikely to leach. The new carrier could be suitable for immobilization of other industrial enzymes. © 2008 Humana Press Inc.